White matter and reaction time: Reply to commentaries. Issue 2 (3rd April 2017) - Voelker, Pascale; Piscopo, Denise; Weible, Aldis P.; Lynch, Gary; Rothbart, Mary K.; Posner, Michael I.; Niell, Cristopher M.
ABSTRACT: We appreciate the many comments we received on our discussion paper and believe that they reflect a recognition of the importance of this topic worldwide. We point out in this reply that there appears to be a confusion between the role of oscillations in creating white matter and other functions of oscillations in communicating between neural areas during task performance or at rest. We also discuss some mechanisms other than the enhancement of white matter that must influence reaction time. We recognize the limited understanding we have of transfer and outline some future directions designed to improve our understanding of this process.